Nutritional Compositions and Phytochemical Properties of the Edible Flowers from Selected Zingiberaceae Found in Thailand - Rachkeeree, Apinya; Kantadoung, Kuttiga; Suksathan, Ratchuporn; Puangpradab, Ratchadawan; Page, Paul Alexander; Sommano, Sarana Rose (Frontiers in Nutrition, 2018)
The nutritional compositions and phytochemical properties of 8 edible flowers of the Ginger family (Zingiberaceae) commonly found in Thailand are reported herein. The plant genera investigated were Zingiber (Ginger, Phlai Dam, Krathue), Hedychium (2 morphological filament forms), Curcuma (Ao), Etlingera (Torch ginger), Amomum (Chi Kuk) and Alpinia (Galangal), which are eaten fresh or cooked as ingredients in the preparation of many Thai dishes. The proximate compositions (moisture, ash, fibre, protein, fat and carbohydrate contents) varied among the different genera. The plants sampled were generally low in fat content (< 1%), which contributed as little as 30% of the total caloric energy. Edible plant parts contained substantially high amounts of potassium (max. 737.21 mg/100g), calcium (max. 140.15 mg/100g), and iron (~0.32 mg/100g). Among the tested samples, torch ginger had the highest vitamin C content (1.05 mg/100g), total phenolic and total flavonoid contents and as well as 2,2-diphenyl-1-picrylhydrazyl (DPPH) acvitivity. On the other hand, the 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assay suggested that Hedychium species possessed the highest antioxidant activity (~5.38 mg TEAC/g extract). Our results prove that edible plants of the Zingiberaceae family found in Thailand are rich sources of potentially important nutrients.